Export quality differentiation under credit constraints - Andrea Ciani; Francesca Bartoli (The World Economy, 2020)
This paper studies the effect of credit constraints on the choice by small and medium-sized enterprises to export goods of higher quality relative to their domestically sold output (quality differentiation). The empirical analysis employs detailed firm-level data on product characteristics and credit scores. Credit constraints are found to be negatively associated with export quality differentiation. Firms reporting a deterioration of the credit score by a standard deviation are 36% less likely to pursue quality differentiation. The negative relation between credit constraints and quality differentiation is stronger for firms exporting to distant markets.
Keywords: 330; credit constraints; distance; heterogeneous firms; product quality